Analysis on the dynamics of flexible drillstring under different drilling parameters - Cao, Jifei; Zou, Deyong; Xue, Qilong; Wang, Jin; Huang, Leilei; Guo, Feng; Wang, Chong; Qu, Jun (Frontiers in Earth Science, 2024)
During the operation of the drill string, it displays a degree of flexibility. Simultaneously, its dynamic properties, influenced by complex stress conditions, manifest nonlinearity and uncertainty. A comprehensive investigation into the dynamics of flexible drill strings is imperative for deep well drilling. This paper presents a model that simulates random interactions between a flexible drill string and the borehole wall, simplifying the actual drill string model using analogous principles. Dynamic simulation software is utilized for analysis, and an indoor experimental setup has been established. The results reveal that with a constant weight on bit (WOB), higher drill string rotational speeds correlate with increased susceptibility to buckling deformation. Additionally, the critical time for deformation onset exhibits a nearly linear relationship with rotational speed. Maintaining a constant rotational speed, an increase in WOB enhances the likelihood of buckling deformation. The experimental findings suggest a correlation between the drill string’s rotation frequency and the WOB.